Optimization and effects of different culture conditions on growth of Halomicronema hongdechloris – a filamentous cyanobacterium containing chlorophyll f - Li, Yaqiong; Lin, Yuankui; Loughlin, Patrick C.; Chen, Min (Frontiers in Plant Science, 2014)
A chlorophyll f containing cyanobacterium, Halomicronema hongdechloris (H. hongdechloris) was isolated from a stromatolite cyanobacterial community. However, the extremely slower growth rate of H. hongdechloris culture became a critical factor, hindering the research on this newly isolated cyanobacterium and the investigation of chlorophyll f-photosynthesis. Therefore, optimizing H. hongdechloris culture conditions has become an essential requirement for future research. This work investigated the effects of various culture conditions, essential nutrients and light environments to determine the optimal growth conditions for H. hongdechloris and the biosynthetic rate of chlorophyll f. Based on the total chlorophyll concentration, an optimal growth rate of 0.22 ± 0.02 day-1 (doubling time: 3.1 ± 0.3 days) was observed when cells were grown under continuous illumination with far-red light with an intensity of 20 µE at 32°C in modified K+ES seawater (pH 8.0) with additional supplements of 11.75 mM NaNO3 and 0.15 mM K2HPO4. High performance liquid chromatography on H. hongdechloris pigments confirmed that chlorophyll a is the major chlorophyll and chlorophyll f constitutes approximately 10% of the total chlorophyll from cells grown under far-red light. Fluorescence confocal image analysis demonstrated changes of photosynthetic membranes and the distribution of photopigments in response to different light conditions. The total photosynthetic oxygen evolution yield per cell showed no changes under different light conditions, which confirms the involvement of chlorophyll f in oxygenic photosynthesis. The implications of the presence of chlorophyll f in H. hongdechloris and its relationship to light environment are discussed.